THE RELATIONSHIP OF PATIENT SATISFACTION WITH LOYALTY OF OUTPATIENTS IN PKU MUHAMMADIYAH HOSPITAL IN DIY - Rosyidah Rosyidah; Ahmad Ahid Mudayana; Siti Kurnia Widihastuti (Universitas Ahmad Dahlan, 2018)
Background: Service is an effort made by the employee to fulfill his customers' wishes with the services to be provided. Satisfaction is one indicator of the quality of service that we provided and patient satisfaction is a capital to get more patients and to get loyal patients. Customer loyalty is determined by the quality of service that shapes the patient's satisfaction resulting in an impact on hospital image and patient confidence. This research aims to. Objective: find out the relationship between service decision and customer loyalty in Muhammadiyah PKU hospital in DIY Methodology: This research type included quantitative research with cross sectional approach. The study was conducted at three PKU hospitals in Yogyakarta. The number of samples in this research amounted to 300 respondents who are patients at the hospital PKU Muhammadiyah in Yogyakarta. The data analysis is used uni-variate and bivariate analysis using chi-square test. Result: The results showed that out of 300 respondents studied, respondents who were less satisfied with the services of PKU Muhammadiyah hospital in Yogyakarta were 193 (64.3%) and respondents who were satisfied with the service of PKU Muhammadiyah hospital in Yogyakarta were 107 (35.7%), respondents who were not loyal to the service of PKU Muhammadiyah hospital in Yogyakarta were 98 (32.7%) and respondents who were loyal to the service of PKU Muhammadiyah hospital in Yogyakarta were 202 (67.3%). The results of bivariate analysis showed that p-value α (0.001 <0.05), so it can be concluded that Ha was accepted and Ho was rejected which meant that there was a relationship between patient satisfaction and patient loyalty in PKU Muhammadiyah hospital in DIY. Conclusion:The level of satisfaction of PKU hospital patients showed that more patients are less satisfied with the higher service compared to patients who are satisfied with the Service, the level of patients who are loyal to the higher service than patients who are not loyal. There is a relationship of patient satisfaction with patient loyalty.